Persepsi Karyawan Tentang Kesadaran K3 & Dampaknya Terhadap Proses Kerja di PT Breadcrumb X: Pendekatan 4M+1E - Ria Sri Amelia; Revanza Fitra Hamdany; Sabilla Sholiah; Andry Putra Pratama; Yudi Prastyo (Journal of Science, Technology, and Innovation, 2025)
Occupational safety and health (OSH) is a crucial aspect in ensuring smooth production processes and protecting workers, especially in the manufacturing industry, which has a high level of occupational risk. This study aims to analyze employees' perceptions of OSH awareness and its impact on work processes at PT Breadcrumb X using the 4M+1E approach. The research method used was descriptive qualitative, with data collection through in-depth interviews, field observations, and documentation of production employees and representatives of the OSH/SHE department. Data analysis was performed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, with data validity maintained through source and method triangulation and member check. The results showed that employees had a basic understanding of K3, but its implementation was inconsistent due to limitations in training, PPE facilities, supervision, and the condition of machinery, work methods, materials, and the work environment, which were risky. These findings confirm that K3 awareness needs to be strengthened through management commitment, work system improvements, and active employee involvement in order to create a sustainable safety culture that supports the effectiveness of work processes..